The risk relationships between alcohol consumption, alcohol use disorder and alcohol use disorder mortality: a systematic review and meta-analysis - Carr, Tessa; Kilian, Carolin; Llamosas-Falcón, Laura; Zhu, Yachen; Lasserre, Aurélie M.; Puka, Klajdi; Probst, Charlotte (Addiction, 2024)
Background and aims: Increasing levels of alcohol use are associated with a risk of developing an alcohol use disorder (AUD), which, in turn, is associated with considerable burden. Our aim was to estimate the risk relationships between alcohol consumption and AUD incidence and mortality. Method: A systematic literature search was conducted, using Medline, Embase, PsycINFO and Web of Science for case-control or cohort studies published between 1 January 2000 and 8 July 2022. These were required to report alcohol consumption, AUD incidence and/or AUD mortality (including 100% alcohol-attributable deaths). The protocol was registered with PROSPERO (CRD42022343201). Dose-response and random-effects meta-analyses were used to determine the risk relationships between alcohol consumption and AUD incidence and mortality and mortality rates in AUD patients, respectively. Results: Of the 5904 reports identified, seven and three studies from high-income countries and Brazil met the inclusion criteria for quantitative and qualitative syntheses, respectively. In addition, two primary US data sources were analyzed. Higher levels of alcohol consumption increased the risk of developing or dying from an AUD exponentially. At an average consumption of four standard drinks (assuming 10 g of pure alcohol/standard drink) per day, the risk of developing an AUD was increased sevenfold [relative risk (RR) = 7.14, 95% confidence interval (CI) = 5.13-9.93] and the risk of dying fourfold (RR = 3.94, 95% CI = 3.53-4.40) compared with current non-drinkers. The mortality rate in AUD patients was 3.13 (95% CI = 1.07-9.13) per 1000 person-years. Conclusions: There are exponential positive risk relationships between alcohol use and both alcohol use disorder incidence and mortality. Even at an average consumption of 20 g/day (about one large beer), the risk of developing an alcohol use disorder (AUD) is nearly threefold that of current non-drinkers and the risk of dying from an AUD is approximately double that of current non-drinkers.